2018
DOI: 10.3390/metabo8030040
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope-Resolved Metabolomics Shows Metabolic Resistance to Anti-Cancer Selenite in 3D Spheroids versus 2D Cell Cultures

Abstract: Conventional two-dimensional (2D) cell cultures are grown on rigid plastic substrates with unrealistic concentration gradients of O2, nutrients, and treatment agents. More importantly, 2D cultures lack cell–cell and cell–extracellular matrix (ECM) interactions, which are critical for regulating cell behavior and functions. There are several three-dimensional (3D) cell culture systems such as Matrigel, hydrogels, micropatterned plates, and hanging drop that overcome these drawbacks but they suffer from technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 62 publications
1
61
0
Order By: Relevance
“…The sample preparation strategy is limited to spheroids with diameters >400-500 µm and with maximum diameters of 900-1000 µm due to potential error-prone handling and growth limitation, respectively. Other studies in tumor spheroid analysis were performed using various culturing and extraction protocols such as (1) gelatinous cultivation of spheroids and methanol-water extraction [21], (2) magnetized cells to form 3D cultures and cold acetonitrile, 70% methanol or 80% acetone extraction [22], (3) gel-based ultra-low attachment plates of 20-25 spheroids per sample followed by derivatization and chloroform/methanol extraction [23]. Overall, most -omics mass spectrometry-based studies on tumor spheroid analysis rely on extraction strategies with cold organic solvents such as methanol, ethanol or isopropanol [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample preparation strategy is limited to spheroids with diameters >400-500 µm and with maximum diameters of 900-1000 µm due to potential error-prone handling and growth limitation, respectively. Other studies in tumor spheroid analysis were performed using various culturing and extraction protocols such as (1) gelatinous cultivation of spheroids and methanol-water extraction [21], (2) magnetized cells to form 3D cultures and cold acetonitrile, 70% methanol or 80% acetone extraction [22], (3) gel-based ultra-low attachment plates of 20-25 spheroids per sample followed by derivatization and chloroform/methanol extraction [23]. Overall, most -omics mass spectrometry-based studies on tumor spheroid analysis rely on extraction strategies with cold organic solvents such as methanol, ethanol or isopropanol [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in tumor spheroid analysis were performed using various culturing and extraction protocols such as (1) gelatinous cultivation of spheroids and methanol-water extraction [21], (2) magnetized cells to form 3D cultures and cold acetonitrile, 70% methanol or 80% acetone extraction [22], (3) gel-based ultra-low attachment plates of 20-25 spheroids per sample followed by derivatization and chloroform/methanol extraction [23]. Overall, most -omics mass spectrometry-based studies on tumor spheroid analysis rely on extraction strategies with cold organic solvents such as methanol, ethanol or isopropanol [21][22][23][24]. This is consistent with our tumor spheroid workflow based on non-scaffold based cultivation on ultra-low attachment plates and the optimized cold 80% methanol extraction with a single washing step.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of drug distributions and effects on downstream pathways via metabolomics approaches has successfully been used to predict antitumour cytotoxic responses by the analysis of extracellular metabolites in cancer patients . These metabolomic studies have been extended to three‐dimensional (3D) cell culture studies, whereby the environment recapitulates the drug resistance seen in vivo , and have further shown that metabolomic profiles may predict the malignant potential of cells grown in 3D cell culture …”
Section: Introductionmentioning
confidence: 99%